Assessment of Stakeholders’ Provision of Infrastructure Facilities for Teaching and Learning in Public Secondary Schools in Benue State, - Nayongo , Victor Terseer; Abdullahi, Barakatu; Gambo , Adamu Aliyu (Kashere Journal of Education, 2025)
This study assessed stakeholders’ provision and maintenance of infrastructural facilities for teaching and learning in public senior secondary schools in the Benue North-East Educational Zone, Nigeria. The study was anchored on Stakeholder Theory (Freeman, 1984) and Maslow’s Theory of Needs (1943), which emphasise the collective responsibility of stakeholders and the satisfaction of essential needs for optimal performance. The study aimed to evaluate the sufficiency of stakeholders’ infrastructural facilities and assess their alignment with current educational requirements. A descriptive survey design was adopted. Data were collected from principals, teachers, and education officers using structured questionnaires. The data were analysed using descriptive and inferential statistics. The findings revealed inadequate infrastructure and that the existing infrastructure does not support effective teaching and learning. It recommended that government and education authorities establish clear maintenance policies and ensure regular supervision. Effective stakeholder engagement will foster ownership, accountability, and improvement in the quality of teaching and learning environments in public secondary schools across the Benue North-East Educational Zone.